First demographic assessment of the recently discovered population of the narrow endemic Femeniasia balearica (Asteraceae) from the Balearic Islands (Western Mediterranean) - Rodríguez, Miquel; Cursach, Joana (Mediterranean Botany, 2024)
Demographic data on threatened species is crucial to understand their conservation status and make management decisions when necessary, which is especially relevant for narrow endemic species with isolated populations. This is the case of Femeniasia balearica (J.J. Rodr.) Susanna, a narrow endemic cushion-like shrub that grows in coastal areas of northern Menorca (Balearic Islands, western Mediterranean Basin) and catalogued as Vulnerable according to the IUCN categories. Recently, a new population has been located in the center of the Serra de Tramuntana of Mallorca (Balearic Islands). In this study, the demographic status of the population from Mallorca has been studied, geolocating all of the individuals with a differential GPS to obtain a detailed map. Data on stage of development (seedling, vegetative or reproductive), morphometry and the overall status of all the individuals have been compiled. A total of 116 individuals and 96 seedlings have been counted. The fact that most of the individuals are reproductive (86.70%) and the confirmation of the presence of seedlings suggest that the population may be maintained in the future. This study provides valuable data on the demographic status of the new population of the species, but long-term monitoring is necessary for analyzing demographic trends.